Cadmium contributes to atherosclerosis by affecting macrophage polarization. (March 2023) - Wan, Yu; Mo, Lijun; Huang, Haibin; Mo, Lifen; Zhu, Wei; Li, Wenxue; Yang, Guangyu; Chen, Linquan; Wu, Yongning; Song, Jia; Yang, Xingfen
Abstract: Chronic cadmium (Cd) exposure contributes to the progression of atherosclerosis, but the direct role of Cd and its mechanisms in atherosclerosis remains incompletely understood. Atherosclerosis is a chronic inflammatory disease promoting macrophage polarization to M1 phenotype and producing pro-inflammations that are vital in regulating the inflammatory response. Herein, through a case-control study, we found that Cd exposure may promote the occurrence of carotid plaque via inflammation, where interleukin-6 (IL-6) may play an important role. We also combined in vivo and in vitro experiments to explore the underlying mechanism of Cd-promoted plaque formation and the production of IL-6. With or without cadmium chloride (CdCl2 ) fed ApoE −/− mouse and treated RAW264.7 cells, we found Cd accumulated in the aortas which significantly increased the plaque area in atherosclerotic mice, macrophage accumulation, and lipid accumulation, and Cd promoted M1 phenotype macrophage polarization reflected by the increased expression of CD86 which produced tumor necrosis factor-α (TNF-α) and IL-6. However, the influences on M2 phenotype and anti-inflammatory cytokines interleukin-4 (IL-4) and interferon-γ (IFN-γ) were non-significant. Moreover, we found that JAK2/STAT3 pathway was greatly activated in the plaques and CdCl2 -treated macrophages. The inhibition of JAK2/STAT3 substantially reversed the Cd-stimulated macrophage M1 phenotype macrophage polarization and the expression of pro-inflammatory cytokines including TNF-α and IL-6. Altogether, Cd intensifies atherosclerosis by modulating macrophage polarization via JAK2/STAT3 to up-regulated the expression of IL-6. Graphical abstract: Image 1